Association between lactate-to-albumin ratio and 28-day ICU mortality in pediatric severe pneumonia patients - Yang Zhang; Rubing Guo; Li Wang; Jihong Hu (PLoS ONE, 2025)
Introduction The lactate-to-albumin ratio (LAR) has emerged as a promising prognostic biomarker in critical care, reflecting both metabolic dysfunction and inflammatory status. However, its prognostic value in pediatric severe pneumonia remains underexplored. This study aimed to investigate the association between LAR and 28-day ICU mortality in pediatric severe pneumonia patients using data from the Paediatric Intensive Care database. Methods A retrospective cohort study was conducted involving 617 pediatric severe pneumonia patients admitted to the ICU between 2010 and 2018. LAR was calculated as the ratio of lactate (mmol/L) to albumin (g/dL). The primary outcome was 28-day ICU mortality. Cox proportional hazards regression models were used to assess the relationship between LAR and mortality, with restricted cubic splines (RCS) employed to explore potential nonlinear associations. Subgroup analyses were performed based on age, sex, and oxygenation status. Results A significant linear relationship was observed between LAR and 28-day ICU mortality. Each unit increase in log (LAR) was associated with a 2.51-fold higher mortality risk (HR 2.51, 95% CI: 1.73, 3.65; P < 0.001). Kaplan-Meier analysis confirmed that patients in the highest LAR tertile had significantly lower survival probabilities compared to those in the lowest tertile (log-rank P < 0.001). Subgroup analyses revealed consistent associations across age, sex, and oxygenation status, with no significant interactions (all P for interaction>0.05). Conclusions Higher LAR levels are independently associated with increased 28-day ICU mortality in pediatric severe pneumonia patients, demonstrating a linear relationship. These findings highlight LAR as a valuable prognostic tool for early risk stratification and clinical decision-making in this population. Further multicenter studies are needed to validate these results and explore interventions targeting LAR reduction to improve outcomes. Trial registration Not applicable.